Comfort Level And Effectıve Factors In Thırd Trımester Pregnancy - Semiha Aydın Özkan; Derya Kaya Şenol; Ergül Aslan (Dokuz Eylul University, 2020)
Background: Pregnancy is a period in which psychological, physiological, emotional changes are experienced and comfort for pregnant women can decrease. Objective: The aim of the study was to determine the prenatal comfort level and the affecting factors in third trimester pregnant women. Methods: This analytical cross-sectional study was conducted between July 2018 and September 2018. The sample consisted of 421 pregnant women in the third trimester who were admitted to the obstetrics and gynecology outpatient clinic of a hospital in Çankırı, who agreed to participate in the study. The data were collected by using the "Pregnant Information Form" and the "Prenatal Comfort Scale" (PCS). Results: Of the pregnant women, 52.3% were in the 26-34 age range, 26.6% were university graduates, 31.1% had low income, 73.6% of them were multiparous and 17.3% of them were not planned pregnancy. The mean PCS and sub-dimensions of the pregnant women were found to be 62.98 ± 8.28, 17.23 ± 2.75, 8.98 ± 1.36, 12.90 ± 2.11, 12.99 ± 1.98, and 10.88 ± 2.87, husband, fetus, people, mother, myself respectively. The PCS scores of the pregnant women were found to be significantly higher in the 18-25 age group, higher education graduates, employee, pregnancy-planned and primipara pregnants (p = .001). As a result of logistic regression analysis performed with these variables, multiparity prenatal comfort (OR = 2.986, 95% C.I 1.529-5.832) was found to be an important variable that affected negatively (p = .001). Conclusion: The prenatal comfort of pregnant women was found to be "high" and were found to be significantly higher in the 18-25 age group, higher education graduates, employee, pregnancy-planned and primipara pregnants. Midwives and nurses; it is thought that evaluation of comfort levels of pregnant women and planning interventions for them are important in terms of preventing negative consequences for pregnancy and postpartum period.